1999
DOI: 10.1002/1529-0131(199910)42:10<2160::aid-anr17>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two schedules for administering oral low-dose methotrexate (weekly versus every-other-week) in patients with rheumatoid arthritis in remission: A twenty-four-week, single-blind, randomized study

Abstract: Objective. To compare the efficacy of 2 low-dose oral methotrexate (MTX) schedules in maintaining remission in patients with rheumatoid arthritis (RA).Methods. Patients with RA were included if they were receiving treatment with weekly MTX for at least 9 months and the RA was in remission (defined by American College of Rheumatology [ACR] criteria) for at least 6 months. Patients were stratified by treatment and randomly assigned to weekly or every-other-weekly (EOW; reducing their monthly dose by half) treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Additionally, no substantial differentiation in PK parameters of MTX was noted with regard to the time of therapy [45]. Similarly, comparison of weekly and every other week regimen by Luis et al concluded that there is no significant difference between the two drug schedules with regard to the efficacy [46]. No major difference in the clinical response as well as the overall change in CRP values was found, when a low daily dose was compared with weekly pulse dose.…”
Section: Measurement Of Ra Disease Activitysupporting
confidence: 89%
“…Additionally, no substantial differentiation in PK parameters of MTX was noted with regard to the time of therapy [45]. Similarly, comparison of weekly and every other week regimen by Luis et al concluded that there is no significant difference between the two drug schedules with regard to the efficacy [46]. No major difference in the clinical response as well as the overall change in CRP values was found, when a low daily dose was compared with weekly pulse dose.…”
Section: Measurement Of Ra Disease Activitysupporting
confidence: 89%
“…However, Pandya et al 22 showed that a twice weekly schedule of methotrexate had no advantage over a weekly schedule. In contrast, a change to every other week dosing was possible in patients stable or in remission on methotrexate, although some experienced disease flares 20 21. In conclusion, weekly methotrexate is the preferred frequency of administration, with a potential switch to a fortnightly schedule in the case of sustained remission.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous studies have reported the high incidence of medication error associated with the weekly dose of MTX 14,20,21 …”
Section: Discussionmentioning
confidence: 99%
“…The main reasons for non‐adherence to MTX are intolerance, forgetfulness and concern about long‐term safety 18 . Some strategies have been proposed to reduce the adverse events or medication errors associated with MTX and improve treatment adherence; for example, by modifying dosage scheme every other week or twice weekly 19–21 . No previous studies comparing clinical outcomes of a total dose divided daily versus the current weekly dosing schedule in RA patients have been performed.…”
Section: Introductionmentioning
confidence: 99%